Herbal Cuscutae Semen Contributes to Oxidative Stress Tolerance and Extends Lifespan via Sirtuin1 in Caenorhabditis elegans - Chunyan Chen; Yudie Liu; Jing Hu; Yihan Gu; Weiwei Li; Hui Yue; Sijing An; Na Sun; Peng Zhang; Nan Li; Lin Miao (Antioxidants)
Cuscutae Semen (CS), a traditional herb recognized as a nutraceutical food in China, has been widely utilized in managing aging-related diseases throughout history. However, whether this mechanism is associated with mitochondrial stress tolerance remains unclear. In the present study, Caenorhabditis elegans (C. elegans) was used to investigate the effects of CS on their longevity. The data demonstrated that CS prolonged the average lifespan of the nematodes by 15.26%, reducing lipofuscin accumulation by 61.46%, as well as improving spontaneous motility. CS treatment significantly enhanced the resistance of C. elegans to hydrogen peroxide-induced oxidative stress and 37 °C induced heat stress, reducing reactive oxygen species (ROS) production by 71.45%. Additionally, membrane potential (MMP) and adenosine triphosphate (ATP) were increased by 354.72% and 69.64%, respectively. However, mitochondrion-specific ROS and calcium flux were significantly reduced to 45.86% and 63.25%, respectively, in C. elegans treated with CS. Consistently, the polymerase chain reaction data revealed that CS significantly up-regulated the expressions of the antioxidant-related genes skn-1, ctl-1, sod-3, and gst-4; the heat shock gene hsp-16.2; and the autophagy-related genes lgg-1 and bec-1. Considering the crucial role of the silent information regulator sirtuin 1 (SIR-2.1/SIRT1) in aging-related mitochondrial oxidative stress, we examined its expression and transcriptional activity. As expected, treatment with CS induced SIRT1 expression, and isorhamnetin identified from CS extract significantly enhanced SIRT1 transcriptional activity in HEK293T cells. Collectively, our results provided evidence that CS prolonged the lifespan of C. elegans by ameliorating oxidative stress damage and mitochondrial dysfunction via SIRT1.